Gambaran Dampak Kemoterapi pada Anak Menurut Orang Tua di Rumah Cinta Bandung : Overview of the Impact of Chemotherapy on Children According to Parents at Rumah Cinta Bandung - Ridha Ranailla; Ai Mardhiyah; Nur Oktavia Hidayati (Fakultas Keperawatan Universitas Andalas, 2016)
Cancer is one of the most frequently diseases among children. Chemoteraphy as primary intervention for cancer in children has so many impacts that effect physical and psychological children. This study aimed to identify the most impact of chemotherapy that children felt severe and bothersome. It was done by assessment to parents in “Rumah Cinta Bandung”. Descriptive quantitative method was used in this research and accidental sampling was used for 45 days to 30 respondent. The data was collected using Symptom assessment in childen receiving cancer therapy: the parent perspective from Lee Dupuis. The data contained of two items those were severe and bothersome with 69 questions for each. Data analysis used frecuency distributive to describe the proportion percentage severe and bothersome impact on chemotherapy and also rank of the most severe and bothersome on chemotherapy impact based on mean score by the assessment to parents. The result was 40% children felt the impact of chemotherapy was severe and 36,7% children felt bother with the impact of chemotherapy based on the assessment to the parents. Psychologial aspect in sub variable for children mood and feeling especially emotional aspect (mood swings and feeling angry) were the most severe mpact that children felt. Meanwhile, the item of physical impact that identified as the most bothersome impact that chidren felt were loss of appetite, nausea, and vomiting. Impact of chemotherapy needed more concerned from parents and care provider because for could bother the children quality of life during the treatment. This result was expected to help in finding the priority of intervention to decrease chemotherapy impact that effect children’s physical, psychology and quality of life.